Corporate Social Responsibility of the Leading Bank Institutions in Poland - Paluszak, Grzegorz; Wiśniewska-Paluszak, Joanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The purpose of this paper is to identify the CSR scopes of the leading bank institutions in Poland and to discuss their strategic context in the light of the theoretical findings. This paper analyzes the scope of practices undertaken by banks that publish Corporate Social Responsibility (CSR) reports. It demonstrates the important role of banks in reporting and introducing corporate social responsibility practices in Poland. This paper uses a content analysis of selected banks’ CSR reports. In the analyzed 2007–2016 period it notes the increasing amount of banks’ reports and reported by them practices. The leading CSR bank institutions covered by this study adopt numerous practices such as, primarily, community involvement and development, including charitable, philanthropic and educational activities as well as entrepreneurship, creating jobs and competencies. Ranked second are labor practices and initiatives, oriented mainly at employee volunteering as well as training and development. The third group are consumer issues, primarily including those focused on rising availability of products and services as well as on facilities for clients. This analysis shows that the leading CSR bank institutions better and better understand the role of corporate involvement in society as a modern strategic approach that leverages capabilities to improve salient areas of competitive context and transforms value chains activities to benefit society while reinforcing corporate strategy.